Activation of Piezo1 contributes to matrix stiffness‐induced angiogenesis in hepatocellular carcinoma - Miao Li; Xi Zhang; Mimi Wang; Yaohui Wang; Jiali Qian; Xiaoxia Xing; Zhiming Wang; Yang You; Kun Guo; Jie Chen; Dongmei Gao; Yan Zhao; et al. (Cancer Communications, 2022)
Abstract Background Despite integrin being highlighted as a stiffness‐sensor molecule in matrix stiffness‐driven angiogenesis, other stiffness‐sensor molecules and their mechanosensory pathways related to angiogenesis in hepatocellular carcinoma (HCC) remain obscure. Here, we explored the interplay between Piezo1 and integrin β1 in the mechanosensory pathway and their effects on HCC angiogenesis to better understand matrix stiffness‐induced angiogenesis. Methods The role of Piezo1 in matrix stiffness‐induced angiogenesis was investigated using orthotopic liver cancer SD rat models with high liver stiffness background, and its clinical significance was evaluated in human HCC tissues. Matrix stiffness‐mediated Piezo1 upregulation and activation were assayed using an in vitro fibronectin (FN)‐coated cell culture system with different stiffness, Western blotting and Ca2+ probe. The effects of shPiezo1‐conditioned medium (CM) on angiogenesis were examined by tube formation assay, wound healing assay and angiogenesis array. The underlying mechanism by which Piezo1 participated in matrix stiffness‐induced angiogenesis was analyzed by microRNA quantitative real‐time polymerase chain reaction (qRT‐PCR), matrix stiffness measurement, dual‐luciferase reporter assay, ubiquitination assay and co‐immunoprecipitation. Results Increased matrix stiffness significantly upregulated Piezo1 expression at both cellular and tissue levels, and high expression of Piezo1 indicated an unfavorable prognosis. High matrix stiffness also noticeably enhanced the activation level of Piezo1, similar to its expression level. Piezo1 knockdown significantly suppressed tumor growth, angiogenesis, and lung metastasis of HCC rat models with high liver stiffness background. shPiezo1‐CM from HCC cells attenuated tube formation and migration abilities of vascular endothelial cells remarkably, and analysis of differentially expressed pro‐angiogenic factors revealed that Piezo1 promoted the expression and secretion of vascular endothelial growth factor (VEGF), CXC chemokine ligand 16 (CXCL16) and insulin‐like growth factor binding protein 2 (IGFBP2). Matrix stiffness‐caused Piezo1 upregulation/activation restrained hypoxia inducible factor‐1α (HIF‐1α) ubiquitination, subsequently enhanced the expression of downstream pro‐angiogenic factors to accelerate HCC angiogenesis. Besides, collagen 1 (COL1)‐reinforced tissue stiffening resulted in more expression of Piezo1 via miR‐625‐5p. Conclusions This study unravels a new mechanism by which the integrin β1/Piezo1 activation/Ca2+ influx/HIF‐1α ubiquitination/VEGF, CXCL16 and IGFBP2 pathway participates in matrix stiffness‐driven HCC angiogenesis. Simultaneously, a positive feedback regulation loop as stiff matrix/integrin β1/miR‐625‐5p/Piezo1 and COL1/stiffer matrix mediates matrix stiffness‐caused Piezo1 upregulation.